2008
DOI: 10.1093/nar/gkn543
|View full text |Cite
|
Sign up to set email alerts
|

A thermodynamic overview of naturally occurring intramolecular DNA quadruplexes

Abstract: Loop length and its composition are important for the structural and functional versatility of quadruplexes. To date studies on the loops have mainly concerned model sequences compared with naturally occurring quadruplex sequences which have diverse loop lengths and compositions. Herein, we have characterized 36 quadruplex-forming sequences from the promoter regions of various proto-oncogenes using CD, UV and native gel electrophoresis. We examined folding topologies and determined the thermodynamic profile fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
74
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 63 publications
7
74
1
Order By: Relevance
“…We did not observe a plateau around a total loop length of ≈7 nt as found by Bugaut and Balasubramanian (17): T m tends to reach a plateau but only for much longer loops (Figures 6 and 7A). The correlation found in Figure 7A is strikingly better than the one observed for naturally occurring sequences (24). In the later case, loop composition plays a predominant role and masks the length effects.…”
Section: Discussioncontrasting
confidence: 52%
“…We did not observe a plateau around a total loop length of ≈7 nt as found by Bugaut and Balasubramanian (17): T m tends to reach a plateau but only for much longer loops (Figures 6 and 7A). The correlation found in Figure 7A is strikingly better than the one observed for naturally occurring sequences (24). In the later case, loop composition plays a predominant role and masks the length effects.…”
Section: Discussioncontrasting
confidence: 52%
“…As compared to duplex DNA, G4s are normally less stable (reviewed in [4], [62], [63]). Thus, high G4 content (abundance) in a particular TRR can enhance the competition of G4 DNA with adjacent duplex DNA, resulting in the increased probability of the involvement of G4s in regulating downstream gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…Both have similar thermal stability (Table 6) as compared to the human telomeric G4 [77], [78], and other G4s with similar loop length, such as MYC, KIT, WNT1 and VEGF G4s [4]. Kinetic stability studies (Table S3) revealed that the unfolding of MNSG4 is entropically driven and that it can unfold relatively easily [79], [80].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works support the important role played by the nature and length of the loops in quadruplex stability (12–22) and reports suggest a strong influence of loop length on quadruplex stability. However, the stability cannot simply be deduced from total loop length, as elegantly demonstrated by Kumar and Maiti (21). …”
Section: Introductionmentioning
confidence: 99%